Discovery and functional characterization of neuropeptides in crinoid echinoderms - Aleotti, Alessandra; Wilkie, Iain C.; Yañez-Guerra, Luis A.; Gattoni, Giacomo; Rahman, Tahshin A.; Wademan, Richard F.; Ahmad, Zakaryya; Ivanova, Deyana A.; Semmens, Dean C.; Delroisse, Jérôme; Cai, Weigang; Odekunle, Esther; et al. (Frontiers in Neuroscience, 2022)
Neuropeptides are one of the largest and most diverse families of signalling molecules in animals and, accordingly, they regulate many physiological processes and behaviours. Genome and transcriptome sequencing has enabled the identification of genes encoding neuropeptide precursor proteins in species from a growing variety of taxa, including bilaterian and non-bilaterian animals. Of particular interest are deuterostome invertebrates such as the phylum Echinodermata, which occupies a phylogenetic position that has facilitated reconstruction of the evolution of neuropeptide signalling systems in Bilateria. However, our knowledge of neuropeptide signalling in echinoderms is largely based on bioinformatic and experimental analysis of eleutherozoans – Asterozoa (starfish, brittle stars) and Echinozoa (sea urchins, sea cucumbers). Little is known about neuropeptide signalling in crinoids (feather stars, sea lilies), which are a sister clade to the Eleutherozoa. Therefore, we have analysed transcriptome/genome sequence data from three feather star species, Anneissia japonica, Antedon mediterranea and Florometra serratissima, to produce the first comprehensive identification of neuropeptide precursors in crinoids. These include representatives of bilaterian neuropeptide precursor families and several predicted crinoid neuropeptide precursors. Using Antedon mediterranea as an experimental model, we have investigated the expression of selected neuropeptides in larvae (doliolaria), post-metamorphic pentacrinoids and adults, providing new insights into the cellular architecture of crinoid nervous systems. Thus, using mRNA in situ hybridisation F-type SALMFamide precursor transcripts were revealed in a previously undescribed population of peptidergic cells located dorso-laterally in doliolaria. Furthermore, using immunohistochemistry a calcitonin-type neuropeptide was revealed in the aboral nerve centre, circumoral nerve ring and oral tube feet in pentacrinoids and in the ectoneural and entoneural compartments of the nervous system in adults. Moreover, functional analysis of a vasopressin/oxytocin-type neuropeptide (crinotocin), which is expressed in the brachial nerve of the arms in A. mediterranea, revealed that this peptide causes a dose-dependent change in the mechanical behaviour of arm preparations in vitro - the first reported biological action of a neuropeptide in a crinoid. In conclusion, our findings provide new perspectives on neuropeptide signalling in echinoderms and the foundations for further exploration of neuropeptide expression/function in crinoids as a sister clade to eleutherozoan echinoderms.